Empowerment administrative Factors and its impact on Performance of the service organization An analytic Research at the Ministry of Interior – General Directorate of Traffic - فيحان, ايثار عبد الهادي; العامري, علاء الدين برع (Journal of Economics and Administrative Sciences, 2016)
AbstractThe research study about the empowerment as an independent variable, in which details include (training and improvement, incentives, information sharing, trust, and delegation), has also focused on the performance of the service organization as a dependent variable in all dimensions which include (improve work efficiency, building the core competencies, focus on the beneficiary of the service, increasing the feeling of satisfaction of the employees, and the organizational support commitment). The research has been based on the opinions of a chosen sample of 75 service officers of the Ministry of Interior who work at the General Directorate of Traffic. The research problem has been identified by the researcher through the field of commensalism with service officers at this directorate. The researcher found that the weak points in the performance of the General Directorate of Traffic came from the lack of knowledge of the empowerment and its relation to the directorate performance at the directorate administration.          The research has tried to pursue the following goals: describe the dimensions of administration empowerment and the performance of the service organization as well as the contribution of the empowerment factors in the improvement of the service organization performance, and test the correlation between them in the directorate.The research has used the Descriptive Analytical Approach in order to achieve the goals above. In the practical part of the research survey, interviews and field commensalism has been conducted by the researcher while in the theoretical part previous studies and researches has been used as well as the Statistical Package for the Social Science program (SPSS) to test the correlation between the different research variables.The research found out from the test and analysis of the assumptions on which the study is based, show that The General Directorate of Traffic performance could improve significantly if it follows the recommendation that is suggested in this research.